Comparing Experiences and Specific Needs of Lesbians, Gays and Bisexuals in Primary Health Care (Catalonia) - Subirana-Malaret, M.; Freude, L.; Gahagan, Jacqueline (Issues in Social Science, 2024)
In recent decades, the inclusion of sexual and gender diversity has become more important for public policies in primary health care. However, the specific needs of LGB populations still need to be taken into account for effective sexual and gender diversity inclusion. Therefore, we conducted a closed-ended, anonymous online survey that included sociodemographic questions, perceptions of respondents’ health status, their primary health care experiences and their priorities concerning primary health care to identify their specific needs in more detail. The survey received 241 responses in 2018 (including lesbians, gays, bisexual men and bisexual women). In this article, we reveal the similarities and differences concerning perceived health, experiences and priorities in primary health care according to users’ sexual orientation. Our results offer new data orientating public policies for LGB individuals in primary health care.